ЗАКОНОМЕРНЫЕ СРАСТАНИЯ МИНЕРАЛОВ В ПЕГМАТИТАХ ИЛЬМЕНСКИХ ГОР - Попов В.А.; Попова В.И.; Поляков В.О. (My University, 2006)
The paper summarized results of investigations of the oriented intergrowths of minerals within pegmatites of the Ilmeny mountains. There are two-feldspars, two-micas, biotite-amphibolc, biotite-pyroxene and pyroxe-ne-amphibole intergrowths revealed in syenite (feldspar and nepheline-feldspar) pegmatites. Orientation of the cxsolution products was studied in "sunstonc" (avcnturine feldspar) and "moonstone" feldspars, nephelines and cancrinites. Corundum-biotitc-feldspar and two-micas intergrowths and exsolutions are characterized in star-co-rundums from corundum-feldspar veins. Syntaxic intergrowths of various amphiboles and chlorites were remarked in pegmatoid ultramafites. The regular quartz-feldspar (graphic) and two-feldspars intergrowths are typical for granite pegmatites; there were also detected two-micas, columbite-samarskite and columbite-ilmenorutile, zircon-xenotime, cassiterite-ilmenorutile and cassiterite-ixiolitc, cassiterite-tantalite, tantalite-stibiotantalite, fer-gusonitc-columbite, pyrochlore-fcrgusonite and beryl-cordierite intergrowths. New laws of intergrowth have been revealed for many pairs of minerals.
Keywords: 549:548:552.322